Geschlechtertypisierungen im Kontext von Familie und Schule. (Verlag Barbara Budrich, 2006)
The yearbook 2006 deals with gender images and gender-typical expectations with which children, adolescents and young adults are confronted in the process of growing up. In addition, new perspectives on gender relations in the family are discussed.